Comparative study of Ni-W/CeO2, Ni-W/y-Al2O3 and Ni-W/HT catalysts for H2 production by steam reforming of bioethanol - Hernández, Paz; Fernández, Arturo; Messina, Sarah (Universidad Autónoma de Nayarit, 2011)
Ni-W catalysts supported on CeO2, Al2O3 and hydrotalcite (HT) were studied in the steam reforming of ethanol at 500-650ºC. The CeO2 and HT were synthesized by impregnation and direct coprecipitation methods, respectively. Commercial Al2O3 was used. Nickel content was varied from 10, 15 and 30% with 1% W. The catalyst that presented the highest catalytic activity and selectivity to hydrogen was 10% Ni-W/HT. Conversion to ethanol was 100% and selectivities to H2, CH4, CO2 and CO were 75, 5.78, 0.37 and 18.85%, respectively, at a temperature of 500ºC. Moreover, these catalysts showed good stability with respect to carbon deposition and low selectivity towards C2H4 production. These are desirable features for catalysts to be used in hydrogen production for fuel cell applications.